2021
DOI: 10.1007/s11920-021-01253-9
|View full text |Cite
|
Sign up to set email alerts
|

Taking Care of Those Who Care: Attending Psychological Needs of Health Workers in a Hospital in Madrid (Spain) During the COVID-19 Pandemic

Abstract: Purpose of Review We aim to review evidence of the psychological impact of the COVID-19 pandemic on healthcare professionals and the effects of the psychological crisis interventions and measures implemented to manage stress. Recent Findings Mental health problems are frequently encountered in health professionals during emergencies and often prevail over the following years. Results show health professionals exhibited symptoms of depression, anxiety, emotional distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“… 41 , 42 Existing guidelines for mental health programs for HCWs recommend easily accessible programs that are brief, simple, and incorporate digital components to augment convenience and accessibility. 43 Facilitators to successful implementation of these programs include a positive, safe learning environment that includes formal and informal discussions and that provides opportunities for reflection and shared learning. 44 PRISM at Work meets all of these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 Existing guidelines for mental health programs for HCWs recommend easily accessible programs that are brief, simple, and incorporate digital components to augment convenience and accessibility. 43 Facilitators to successful implementation of these programs include a positive, safe learning environment that includes formal and informal discussions and that provides opportunities for reflection and shared learning. 44 PRISM at Work meets all of these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive systems should be established to assess and monitor the psychological well-being of different professional groups in primary care and facilitate their access to psychological help. 62 Additionally, interventions should be conducted to promote resilience, as it is a modifiable factor, 63,64 implementing strategies focused on self-care and changes in the organisation and work environment. 65,66 Longitudinal studies are necessary to assess the evolution of the psychological impact of the pandemic over time and to identify the factors that determine or can predict this evolution.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Similarly, a study of medical staff in Hubei, China [ 26 ] found that staff often worried about their family, with the worry being highest in the age group most likely to have young families. This ties into an identified risk factor for psychiatric symptoms: having dependent children [ 27 ]. These worries were amplified in our study through significant financial instability of the island following the economic crisis [ 11 ] and supported by the survey responses and group interviews of the hospital employees.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators can signal early stages of burnout in the hospital staff and can affect the delivery of patient care. Looking at other studies, MH problems are frequently encountered in medical staff during health crises and can have a lasting impact [ 27 ]. Healthcare workers were faced with an increased degree of stress, anxiety, depression, and insomnia due to the COVID-19 pandemic [ 6 ], with some reporting anxiety rates among HWF twice as often as prior to the pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation